THE EVOLUTION OF ENVIRONMENTAL PARTIES AND GREEN POLITICAL MOVEMENTS IN THE REPUBLIC OF SERBIA - Pavlović, Jovica (Politička revija, 2024)
The following work aims to provide an analytical overview of the development of environmental political parties in Serbia. By relying on the methods of process tracing, as well as on Lipset and Rokkan’s and other relevant theories of sociopolitical cleavages, the work examines how political events that occurred in Serbia over the last three decades led to the formation of eco-activist movements and parties, especially within the last several years. More specifically, the fulfillment of the primary aim requires – but is not limited to – an analysis of how green parties and environmental movements formed, shaped, and changed their strategies over time, especially when it comes to their activity planning, decision-making, support-mobilizing, and networking (including participation in broader political coalitions). The study not only includes genuine eco-activist organizations but also focuses on how (and why) decoy and phantom green parties developed and evolved in relation to the activities of their authentic counterparts. The paper concludes that environmental issues became increasingly more important in Serbia during the previous decade, with a more prominent arrival of foreign industry and foreign investors, which consequentially caused a noticeable deterioration of the environment (quality of air in particular). This opened a window of opportunity for opposing movements and parties to attract widespread support – and develop their strategies – based on and in relation to this previously less important topic.
Keywords: Environment; Green Politics; Political parties; Democratization; Serbia